HIV-1 Vif protein blocks the cytidine deaminase activity of B-cell specific AID in E-coli by a similar mechanism of action - Santa-Marta, Mariana (2015)
HIV-1 Vif protein protects viral replication in non-permissive cells by inducing degradation of APOBEC3G via ubiquitination and proteasomal pathway, although new studies indicate a putative role in Vif's direct inhibition of APOBEC3G. APOBEC3G is member o